Impact of Zostavax Vaccination on T-Cell Accumulation and Cutaneous Gene Expression in the Skin of Older Humans After Varicella Zoster Virus Antigen–Specific Challenge. (22nd September 2018) - Patel, Neil P; Vukmanovic-Stejic, Milica; Suarez- Farinas, Mayte; Chambers, Emma S; Sandhu, Daisy; Fuentes-Duculan, Judilyn; Mabbott, Neil A; Rustin, Malcolm H A; Krueger, James; Akbar, Arne N
Abstract: Background: The live attenuated vaccine Zostavax was developed to prevent varicella zoster virus (VZV) reactivation that causes herpes zoster (shingles) in older humans. However, the impact of vaccination on the cutaneous response to VZV is not known. Methods: We investigated the response to intradermal VZV antigen challenge before and after Zostavax vaccination in participants >70 years of age by immunohistological and transcriptomic analyses of skin biopsy specimens collected from the challenge site. Results: Vaccination increased the proportion of VZV-specific CD4 + T cells in the blood and promoted the accumulation of both CD4 + and CD8 + T cells in the skin after VZV antigen challenge. However, Zostavax did not alter the proportion of resident memory T cells (CD4 + and CD8 + ) or CD4 + Foxp3 + regulatory T cells in unchallenged skin. After vaccination, there was increased cutaneous T-cell proliferation at the challenge site and also increased recruitment of T cells from the blood, as indicated by an elevated T-cell migratory gene signature. CD8 + T-cell–associated functional genes were also highly induced in the skin after vaccination. Conclusion: Zostavax vaccination does not alter the abundance of cutaneous resident memory T cells but instead increases the recruitment of VZV-specific T cells from the blood and enhances T-cell activation, particularly cells of the CD8 + subset, in the skin after VZV antigen challenge.